The crescent kick (tendangan sabit) skills of pencak silat athlete khandara khatulistiwa - Hambali, Ibnu; Supriatna, Eka; Rubiyatno, Rubiyatno (Jurnal Patriot, 2025)
Problems: This Self-defense martial arts is sport native to Indonesia. In the event there are noor kembang kembang and fight. In fight martial artist must control various techniques for get points. One of the deadly techniques is a kick sickle. This technique besides turning off also not easy studied. Purpose: Study aimed to get an overview of kicking technique capabilities sickle on one Silat in Pontianak club, West Kalimantan. Method: Survey research, the instruments used by ovservation ceck list. Which consist of 8 items, with range score 1-4. Each athlete get three times chance. Data analyzed with using descriptive statistics by exel and SPSS IBM 22. Results: Research results shows, it turns out ability kick sickle martial artist is in the category good and Mostly very good. Conclusion study This convincing that martial artists in perguruan Pencak Silat Khandara Khatulistiwa Pontianak West Bornea, the ability kick in pencak silat was good and very good levels. Conclusion: Based on the data that has been obtained can concluded that ability kick sickle at college Khandara Equatorial Pencak Silat is very good. Based on this data, trainers can increase the efficiency and effectiveness of sickle kicks by improving biomotor abilities. In this way, coaches can improve the efficiency of the sickle kick by developing the athlete's biomotor skills. Furthermore, a structured training program tailored to the athlete's needs can help improve the athlete's sickle kick performance.